Achieving faster handovers in mobile WiMAX networks - Lu, Qi (2013)
WiMAX is a wireless metropolitan area network (WMAN) specified by IEEE 802.16. It provides the broadband wireless access for mobile devices. In such a system, to enable the mobility, the handover is supported to maintain the connectivity of the mobile station (MS) when it moves from the coverage of the serving base station (BS) to the coverage of a neighbor BS. In the handover process, scanning is required to find a suitable target BS, and network re-entry is needed to establish the new connection. However, in the standard handover process, a long latency to data transmissions is caused resulting in the serious interruption to ongoing services. In this paper, an improved handover scheme is proposed to reduce the latency introduced in the handover process by shortening the scanning and enhancing the network re-entry. The proposed scanning strategy reduces the latency by reducing the number of neighbor BSs to be scanned through estimating the rough location of the MS. The enhanced network re-entry reduces the delay by updating transport connection identifiers (CIDs) early to allow the fast resumption of active applications. Simulations were conducted to evaluate the performance of the proposed handover scheme. The results show that the proposed handover scheme reduces the data transmission latency during handover significantly.